The median effective dose of ciprofol combined with a low-dose sufentanil for gastroscopy in obese or nonobese patients: a dose-finding study using Dixon’s up-and-down method - Zhao, Jie; Zhang, Yixiao; Su, Guowei; Wang, Shaoyi; Zhang, Xiaolin; Wang, Guoxiang; Chen, Gang (Frontiers in Pharmacology, 2025)
ObjectivesUnderstanding the different pharmacodynamic responses to narcotics in patients with or without obesity is particularly important for the safety of gastroscopy sedation. This study aimed to determine the median effective dose (ED50) of ciprofol combined with low-dose sufentanil to inhibit the response to gastroscope insertion in obese or nonobese patients.MethodsA total of 27 obese patients (BMI 30–40 kg/m2) and 25 nonobese patients (BMI 18–25 kg/m2), aged between 18 and 65 years, with ASA physical status of 1–2, were included in this study. All patients underwent painless gastroscopy and received intravenous sufentanil at a dose of 0.1 μg/kg, followed by ciprofol administration. The initial dose of ciprofol for the first patient in both groups was 0.4 mg/kg, the subsequent dose was determined by the response of the previous patient to gastroscope insertion (cough, choking, body movement, etc.) using Dixon’s up-and-down method. The dose was increased or decreased by 0.05 mg/kg depending on the observed responses. Data collection continued until 7 crossover points were obtained. Probit regression and bootstrapping methods were employed to calculate the median effective dose (ED50) and 95% confidence intervals (CIs). The ED50 values were then compared between the obese and nonobese patient groups.ResultsThe ED50 of ciprofol combined with sufentanil inhibiting response to gastroscope insertion in patients with obesity was 0.186 mg/kg with 95% CI of 0.153∼0.209 mg/kg, was significantly lower than patients with nonobese was 0.237 mg/kg with 95% CI of 0.206∼0.253 mg/kg (p < 0.05).ConclusionThe ED50 values of ciprofol combined with sufentanil inhibiting response to gastroscope insertion in patients with obesity was lower than in patients with normal weight.Trial registrationhttps://www.chictr.org.cn/bin/project/edit?pid=202873, identifier ChiCTR2300074216.